Semantic Shift of English Internet Slangs Used in Social Media: Morphosemantic Analysis - Oon Suzana Rahman; Cece Sobarna; Eva Tuckyta Sari Sujatna; Lia Maulia Indriyani (Research And Innovation In Language Learning (RILL), 2022)
The aim this research are to identify the most common morphological process through word formation  found in the lexical of English Internet slang, and to identify the most common type of shift of meaning used by netizen on social media.The research Methodology applied in this research is descriptive qualitative-textual analysis (Bhawna & Gobind (2015) and Smith (2017). The data sources are taken from facebook, twitter and teenage English Slang that are selectively chosen on the basis of criteria.The Theory of English Internet Slang taken from Crystal (2003, 2005,  2011, 2013), Gua and Dai (2019). The research findings are:No Morphological process 72% , derivation  consisted of  16%, Compounding 4%, Coinned 4%, Clipping 4%. Whereas  the type of semantic changes, mostly  narrowing consists of 78%, The words that do not change the meanings are 28%. It is recommended for further reseach which is still open for semantic field, especially under the discussion on figurative meaning Tujuan peneltian ini adalah untuk mengidentifikasi proses morfologi yang paling banyak ditemukan di dalam pembentukan kata internet slang berbahasa Inggris,  dan untuk mengidentifikasi jenis pergeseran makna yang paling banyak digunakan dalam kata  internet slang berbahasa Inggris. Metodologi penelitian yang digunakan yaitu descriptive qualitative –textual analysis dari (Bhawna & Gobind (2015) and Smith (2017). Teori Internet Slang Berbahasa Inggris yang digunakan dalam penelitian berasal dari Crystal (2003, 2011, 2013), Gua dan Dai (2019).Temuan penelitian ini yaitu: tidak terjadi proses morfologis 72%, derivation  consisted of  16%, Compounding 4%, Coinned 4%, Compounding 4%. Sedangkan jenis perubahan semantik, yaitu: narrowing yang terdiri dari 72%, Makna kata yang tidak mengalamii pergeseran, yaitu 28 %. Peneliti merekomendasikan untuk penelitian selanjunya  yang  masih terbuka terutama di bidang semaantik dalam pembahasan makna figurative